Effects of the welding inclusion and notch on the fracture behaviors of low-alloy steel - Guowei Chen; Hongyun Luo; Haoyu Yang; Zhiyuan Han; Zhenying Lin; Zheng Zhang; Yuqin Su (Journal of Materials Research and Technology, 2019)
Effects of the welding inclusions and notches on the deformation and fracture behaviors of low-alloy steels were investigated by combining the tensile performance testing and acoustic emission (AE). The micro-structures and fracture surfaces of the hot-rolled and welded samples were observed by OM and SEM. It was found out that the welding inclusions and notches would result in negative impacts on the mechanical properties of low-alloy steel. During the fracture process of the welds, there were four groups of the AE frequencies, representing three kinds of deformation and fracture behaviors: plastic deformation of the welding matrix, fracture of the welding matrix, and fracture or interface detachment of the welding inclusions. Plastic deformation of the welding matrix mainly took place in the plastic stage and the late hardening stage. Fracture of the welding matrix and inclusions were concentrated in the first half of the hardening stage. Keywords: Welding inclusions, Notch, Fracture behaviors, Acoustic emission, Low-alloy steel